2021
DOI: 10.1021/acsanm.0c03224
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic AuPd Nanoparticles Loaded on Amine-Functionalized Porous Boron Nitride Nanofibers for Catalytic Dehydrogenation of Formic Acid

Abstract: Formic acid (FA) has been considered as a promising hydrogen energy carrier due to its nontoxicity, high energy density, easy storage/transport, etc. However, the development of decent FA dehydrogenation catalysts with high selectivity, good catalytic activity, and excellent cycling performance remains a challenge. Herein, a highly stable heterogeneous catalyst using porous boron nitride nanofibers (BNNFs) as carriers has been developed for catalytic FA dehydrogenation. Taking the advantage of porous BNNFs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 49 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…Alloying Pd with other elements such as Cu, Ni, Ru, Ag, or Au can further optimize the electronic structure of Pd for enhanced activity and stability [15][16][17][18][19][20]. Among various metals, Au is particularly attractive for the exploration of Pd-based binary systems because it contributes to the stabilization of Pd by inhibiting its dissolution under acidic high oxidation conditions, while pure Au itself is inert to FAOR [21,22]. Experimentally, Pd-Au bimetallic catalysts indeed demonstrate improved performance, which are attributed to the possible fundamental issues including geometric effect, electronic effect, faceting, or strain effect [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Alloying Pd with other elements such as Cu, Ni, Ru, Ag, or Au can further optimize the electronic structure of Pd for enhanced activity and stability [15][16][17][18][19][20]. Among various metals, Au is particularly attractive for the exploration of Pd-based binary systems because it contributes to the stabilization of Pd by inhibiting its dissolution under acidic high oxidation conditions, while pure Au itself is inert to FAOR [21,22]. Experimentally, Pd-Au bimetallic catalysts indeed demonstrate improved performance, which are attributed to the possible fundamental issues including geometric effect, electronic effect, faceting, or strain effect [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the h-BN surface lacks defective sites, which does not facilitate the introduction of sufficient polar groups. To solve this problem, h-BN was modified by covalent or noncovalent functionalization schemes, including defect site derivatization, Lewis acid–base interaction, radical covalent functionalization, etc. For example, Huang and co-workers have introduced −NH 2 into porous boron nitride nanofibers to boost the H 2 generation from FA dehydrogenation of the AuPd catalyst . Chermahini and co-workers have demonstrated that hydroxyl-functionalized BN nanosheet-supported AuPd exhibits superior catalytic performance for FA dehydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…Among a plethora of support materials utilized for the synthesis of nanostructured catalysts, exfoliated two-dimensional nanomaterials derived from layered graphene-like materials, particularly hexagonal boron nitride ( h -BN) nanosheets, have received enormous interest as featured support owing to their unique structural and morphological attributes, including a large surface-area-to-volume ratio; high thermal conductivity; excellent mechanical, thermal, and chemical strength; high oxidative resistance; nanometer size; coordinatively unsaturated edge sites; and the capability of dissipating substantial heat in exothermic reactions. Besides, as a consequence of their exclusively stacked nanosheets comprising B and N atoms, fascinating advantages of high complex loading can be readily attained. The soft chemical exfoliation process frequently adopted for the synthesis of h -BN nanosheets allows for great flexibility in controlling the chemical composition and their crystalline structure, ultimately aiding in the formation of 2D inorganic nanosheets possessing rich functionalities that can be further tailored as per the catalytic applicability. Besides layered nanostructures, h -BN nanomaterials comprising different morphologies exhibit prospective application potential in the realm of catalysis. Further, to enhance the separability of these catalytic systems, magnetic components such as Fe 3 O 4 NPs are integrated with these nanostructures, leading to the formation of novel h -BN/Fe 3 O 4 nanocomposites. Undeniably, the magnetic field-assisted separation remains the greenest mode of isolating and retrieving nanoparticles from the reaction mixture as it negates the use of any external solvent and saves time, energy, and catalyst loss. To date, only a very few h -BN nanosheet-supported catalysts have been fabricated for catalyzing important organic reactions.…”
Section: Introductionmentioning
confidence: 99%